P647 Post-marketing evaluation of reported adverse events of a multi-strain probiotic product confirms that change in manufacturing site had no impact on safety profile. (15th January 2020) - Panetta, V; Simonelli, I; Bacchieri, A; Papetti, S; De Stefani, E; Colombo, S
Abstract: Background: In 2016, the manufacturing site of the multi-strain probiotic product VSL#3 changed. The present work is aimed at verifying if this change had an impact on the safety profile of the product. Methods: The safety reports from post-marketing surveillance in the USA received by Alfasigma in the years 2014–2015 were compared with those received in the years 2017–2018. 2016 was not considered, because the product on the market during this year could likely come from both manufacturing sites. VSL#3 is sold in the US market as a medical food. Most of the reports were from consumers and were not medically confirmed. However, this happened in both periods, so no bias is introduced in the comparison. Each single safety report contained one or more adverse events (AEs), coded with MedDRA. The comparison between the two periods concerned primarily the number of safety reports in relation to the number of units sold. Given the similarity of trends between the total number of safety reports and sales in the two periods, the frequencies of the AEs and serious AEs were also compared at the System Organ Class (SOC) and Preferred Term (PT) level. Results: More than 70% of subjects reporting an AE were women in both periods under comparison; mean age was 58; phone was the most frequent means (overall 76%). Table 1 summarises the main results. Sales and number of safety reports were higher in the second than in the first period. However, the ratio between number of reports and sales was higher in the 2014–2015 period compared with the 2017–2018 period: 3.5 vs. 2.9 reports per 10, 000 units sold, respectively. Similar results were obtained when stratifying the described ratios by formulation. The percentages of reports with at least one serious AE were respectively 3.2% in the first period and 2.5% in the second. The two periods appeared to be similar even with respect to the percentages of AEs and serious AEs by SOC and PT, being the AEs under the Gastrointestinal SOC the most frequently reported, as expected. Conclusion: The analyzed data show that the manufacturing site change had no impact on the safety profile of VSL#3.